Play in the early years - Fleer, M. (b)
Play is crucial to the learning and development of children in the early years. The third edition of Play in the Early Years is a comprehensive introduction to the theory and practice of play for children from birth to 8 years old. Drawing on classical and contemporary theories, this text examines social, cultural and institutional approaches to play, and explores a range of strategies for successfully integrating play into early years settings and primary classrooms. This edition features a new chapter on conceptual playworlds, which demonstrates what conceptual playworlds look like to infants and toddlers, pre-schoolers, and children transitioning into school. The text features classroom vignettes and photographs designed to help students connect theory to practice, and reflection questions and research activities encourage in-depth reflection and extend learning. Highly regarded by early childhood researchers and practitioners alike, Play in the Early Years remains an essential resource for pre-service students.
Includes references and index.